Primary chaetotaxy of the larval head capsule and head appendages of the Hydrophilidae (Coleoptera) based on larva of Hydrobius fuscipes (Linnaeus, 1758) - Fikáček, Martin (2008)
The primary chaetotaxy of the larval head capsule and head appendages of the family Hydrophilidae (Insecta:Coleoptera) is described and illustrated using the larva of Hydrobius fuscipes (Linnaeus, 1758) as a model, and comparedwith fifteen hydrophilid taxa representing all main taxonomic groups within the family; brief comparative notes with representativesof the families Helophoridae, Spercheidae, Hydrochidae and Histeridae are also provided. Primary chaetotaxicnomenclature is developed for the Hydrophilidae, allowing the use of chaetotaxic characters for phylogeneticstudies as well as diagnostic purposes. The study of representatives of the families Helophoridae, Hydrochidae andSpercheidae suggests that this nomenclature can also be effectively applied to other hydrophiloid families. Chaetotaxicnomenclature systems used in larvae of other groups of Coleoptera are briefly reviewed.